The reality of developing educational patterns in Syrian universities between (2004 and 2010) (Open and parallel education are two models) - حسن, ميسون (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The reformulation of the educational policy in the Syrian Arab Republic, with its plans and strategies, and its programming within the framework of development adopted by the Syrian vision in the reform program proposed for educational innovations in the types of education through which it is possible to face the increasing numbers in university education for students, and to limit the orientation of Syrian students to Arab and foreign universities and what results. This includes burdens incurred by the national economy, as well as with the aim of achieving self-resources that enhance financial capacity and increase opportunities for enrollment in higher education in Syrian universities. The research aims to study the development of education patterns in Syrian universities for open and parallel education between (2004 and 2010), by studying the reality and development of higher education in Syrian universities, a descriptive and analytical study during the period (2004-2010), according to the data available from the Ministry of Higher Education And the Directorate of Planning and Statistics, the State Planning Commission, calculating some educational indicators, and calculating the equation of the general trend of the relationship between the numbers of undergraduate students, and the time in Syrian universities to measure the average increase and growth during the study period 2004-2010, and estimate their numbers until the year 2020, and after study and analysis The research reached the following results: 1- The total number of undergraduate students (parallel education) increased annually by / 7861 / male and female students, that is, an average increase of / 49.15% / during the period (2004-2010) and that they will increase on average annually, i.e. an average increase rate of / 4.1% /. The number of open education students increased on average annually by / 22107 / male and female students, that is, an average increase of / 88.66% / and that the relationship between the total number of students for open and parallel education and time is positive and very strong. 2- That the number of undergraduate students (parallel education) will increase on average annually by / 8377 / male and female students, that is, an average increase of / 15.86% / during the period (2011-2020); The number of open education students will increase on average annually by / 20311 / male and female students, that is, an average increase of / 11.56% /. 3- Some of the research proposals include conducting more studies dealing with other areas in the system of education patterns, employing technology, spreading awareness of its use, and working to provide educational opportunities that are commensurate with the economic conditions of learners.